Effects of syllable stress in adaptation to altered auditory feedback in vowels - Bakst, Sarah (J Acoust Soc Am, 2021)
Unstressed syllables in English most commonly contain the vowel quality [ə] (schwa), which is cross-linguistically described as having a variable target. The present study examines whether speakers are sensitive to whether their auditory feedback matches their target when producing unstressed syllables. When speakers hear themselves producing formant-altered speech, they will change their motor plans so that their altered feedback is a better match to the target. If schwa has no target, then feedback mismatches in unstressed syllables may not drive a change in production. In this experiment, participants spoke disyllabic words with initial or final stress where the auditory feedback of F1 was raised (Experiment 1) or lowered (Experiment 2) by 100 mels. Both stressed and unstressed syllables showed adaptive changes in F1. In Experiment 1, initial-stress words showed larger adaptive decreases in F1 than final-stress words, but in Experiment 2, stressed syllables overall showed greater adaptive increases in F1 than unstressed syllables in all words, regardless of which syllable contained the primary stress. These results suggest that speakers are sensitive to feedback mismatches in both stressed and unstressed syllables, but that stress and metrical foot type may mediate the corrective response.